General characteristics of otorhinolaryngology consultations: 3-year analysis - Topuz, Muhammet Fatih (Journal of Surgery and Medicine, 2020)
Aim: Nowadays, with the rapid development and change of knowledge in the scientific field, the number of specialty branches in medicine has increased. Therefore, the rate of consultation requests in different specialties during the patient evaluation process gradually escalates. This study aims to evaluate the characteristics of the diagnostic and therapeutic consultations requested from the Otorhinolaryngology (ENT) branch in a university hospital. Methods: In this cross-sectional study, the data of patients consulted to the ENT clinic of Kütahya University of Health Sciences Evliya Çelebi Training and Research Hospital between January 1st, 2017 and December 31st, 2019 were retrospectively scanned. Apart from demographic findings such as age and gender, departments requesting the consultation, post-consultation diagnoses and surgical treatments performed by an ENT physician were noted. Results: The total number of patients with an ENT consultation was 2340. The mean age of the patients was 45.95 (25.09) years. Most consultation requests were made from the emergency department (n=877, 37.5%), which was followed by 278 requests (11.9%) by the neurology and neurology ICU departments, and 193 (8.2%) requests by the anesthesiology and intensive care unit (ICU) departments. Although varying among age groups, epistaxis (10%) and vertigo (dizziness) (10%) were the most common diagnoses. A total of 146 patients received surgical treatment. The most common surgical operations were tracheotomy and nasal bone fracture reduction. Conclusion: Determining the characteristics of patients for whom ENT consultation is required will be beneficial in shaping the training programs for other clinics, reducing unnecessary consultation requests, thus reducing the workload of ENT physicians.